Manuscript Review at the Journal of Pediatric Gastroenterology and Nutrition: The Impact of Reviewers on Editor Decisions. Issue 5 (24th November 2021) - Kumar, Prerna; Ravindra, Aditya; Wang, Yanzhi; Belli, Dominique C.; Heyman, Melvin B.; Gupta, Sandeep K.
ABSTRACT: Objective: Given the importance of scholarly work in academic medicine, better understanding of the manuscript review process (MRP) is useful for authors, reviewers, and editorial boards. We aim to describe the MRP at the Journal of Pediatric Gastroenterology and Nutrition ( JPGN ), assess the correlation between editor decisions and reviewer recommendations, and provide transparency to this process. Methods: All manuscripts submitted in 2018 to JPGN were included in this analysis. Data included reviewers' manuscript scores and recommendations, time spent on each review by reviewers, the editor's rating of the reviewers' reviews, the editor's first decision, and final outcome. Data were collated using the JPGN manuscript submission website, Editorial Manager. Results: 1023 manuscripts were submitted to JPGN in 2018 and included in this analysis. Of these, 486 manuscripts had at least two peer reviewers. The recommendations of the two reviewers were in agreement 43% of the time. Intra-class correlation (ICC) between the two reviewers suggests moderate agreement (ICC = 0.40). When both reviewers agreed to Not Reject (289/486), the editor agreed in 93% of cases (269/289). When both reviewers agreed to Reject (55/486), the editor agreed 100% of the time (55/55). The reviewers disagreed in about one-third of submissions (142/486), and the editor recommended to Reject in two-thirds of these cases (95/142). Overall, inter-reviewer agreement strongly correlated with the editor's initial decision ( P < 0.001). Conclusions: The editor most often agreed with reviewers' assessments when there was concordance between the two reviewers' recommendations. About a third of peer reviews result in discordant recommendations between the two reviewers.